Insights on the functional composition of specialist and generalist birds throughout continuous and fragmented forests - dos Anjos, Luiz; Bochio, Gabriela Menezes; Medeiros, Hugo Reis [UNESP]; Almeida, Bia de Arruda; Lindsey, Barbara Rocha Arakaki; Calsavara, Larissa Corsini; Ribeiro, Milton Cezar [UNESP]; Domingues Torezan, José Marcelo (Wiley, 2019)
A decline in species number often occurs after forest fragmentation and habitat loss, which usually results in the loss of ecological functions and a reduction in functional diversity in the forest fragments. However, it is uncertain whether these lost ecological functions are consistently maintained throughout continuous forests, and so the importance of these functions in continuous forests remains unknown. Point counts were used to assess both the taxonomic and functional diversity of specialist and generalist birds from sampling in a continuous primary forest compared with forest fragments in order to investigate the responses of these groups to forest fragmentation. We also measured alpha and beta diversity. The responses of specialists and generalists were similar when we assessed all bird species but were different when only passerines were considered. When examining passerines we found lower total taxonomic beta diversity for specialists than for generalists in the continuous forest, while taxonomic beta diversity was higher in the fragmented forest and similar between bird groups. However, total functional beta-diversity values indicated clearly higher trait regularity in continuous forest for specialists and higher trait regularity in fragments for generalists. Specialists showed significantly higher functional alpha diversity in comparison with generalists in the continuous forest, while both groups showed similar values in fragments. In passerines, species richness and alpha functional diversity of both specialist and generalist were explained by forest connectivity; but, only fragment size explained those parameters for specialist passerines. We suggest that considering subsets of the community with high similarity among species, as passerines, provides a better tool for understanding responses to forest fragmentation. Due to the regularity of specialists in continuous forest, their lost could highly affect functionality in forest fragments.
Keywords: beta diversity; forest fragments; functional diversity; passerines birds; southern Brazil